Struktur Anatomi Daun Artemisia cina Berg. Ex Poljakov Hasil Kultur Jaringan - Ermayanti, Tri Muji; Juliarni, Juliarni; Andry, Yuli (Universitas Atma Jaya Yogyakarta, 2004)
This study was conducted to investigate the anatomical structure of leaves of Artemisia cina Berg. ex Poljakov due to variances in leaf morphology during grown in vitro. Shaking of culture, position of stem nodes used as explants and concentration of BAP (Benzyl Amino Purin) added to the culture medium were the factors investigated in this study. There was variation in leaves morphology of culture, however this variation did not occur after aclimatization and plant grown in the greenhouse. BAP decreased the level of chlorophyll content of leaves. In general, anatomical characters of leaves were not influenced by shaking, nodes position of stem and level of BAP.